2017
DOI: 10.1262/jrd.2017-058
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of zygotic gene activation by chromatin structure and epigenetic factors

Abstract: After fertilization, the genomes derived from an oocyte and spermatozoon are in a transcriptionally silent state before becoming activated at a species-specific time. In mice, the initiation of transcription occurs at the mid-one-cell stage, which represents the start of the gene expression program. A recent RNA sequencing analysis revealed that the gene expression pattern of one-cell embryos is unique and changes dramatically at the two-cell stage. However, the mechanism regulating this alteration has not yet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Studies have shown that when chromatin reprogramming happens, regulatory factors that are associated with gene transcription and DNA recombination are recruited by chromatin [87, 88], and simultaneously the stability of nucleosome is altered [89]. During zygote gene activation, the activity of open chromatin is increased, in parallel with activities of cis -regulatory factors, which confirms that cis -regulatory elements play a significant role in early development [90, 91]. ATAC-seq has been used, together with the CRISP/Cas-9 technology, to detect mouse preimplantation embryos [61].…”
Section: Summary Of the Atac-seq Methodsmentioning
confidence: 90%
“…Studies have shown that when chromatin reprogramming happens, regulatory factors that are associated with gene transcription and DNA recombination are recruited by chromatin [87, 88], and simultaneously the stability of nucleosome is altered [89]. During zygote gene activation, the activity of open chromatin is increased, in parallel with activities of cis -regulatory factors, which confirms that cis -regulatory elements play a significant role in early development [90, 91]. ATAC-seq has been used, together with the CRISP/Cas-9 technology, to detect mouse preimplantation embryos [61].…”
Section: Summary Of the Atac-seq Methodsmentioning
confidence: 90%
“…Following fertilization, the zygotic genome is globally demethylated 6 , and this loss of DNA methylation coincides with global decreases in repressive histone modifications 5,7 . Overall, epigenetic factors linked to relaxed chromatin are more abundant in mouse zygotes, whereas factors implicated in chromatin compaction become more prevalent during EGA 8 , pointing to a more permissive chromatin landscape in pre-EGA embryos. Indeed, mouse zygotes present increased histone mobility 9 , highly dispersed chromatin 10 , and lack chromocenters (congregations of pericentromeric heterochromatin) 11,12 .…”
mentioning
confidence: 98%
“…Minor ZGA that occurs at the one-cell stage is promiscuous and over 90% of genes (including extensive intergenic regions) are transcribed, mainly with poor splicing and 3ʹ processing. Major ZGA takes place at the two-cell stage, where less than 80% of genes are selectively transcribed, probably due to a condensed chromatin state [60]. Recently, it was confirmed that minor ZGA is critical for mouse PED [61].…”
Section: Discussionmentioning
confidence: 99%